A Study on Economic Development Under Mughal Rule in Kashmir - Kumar, Arun (Integrated Journal for Research in Arts and Humanities, 2023)
The Mughal period in Kashmir emerged as a defining era, characterized by transformative socio-economic and cultural shifts. This research delves into the multifaceted influence of the Mughal Empire on Kashmir, examining the administrative reforms, economic prosperity, architectural marvels, and the intertwining of Mughal and Kashmiri identities. While the region thrived under the Mughals, experiencing urban growth, trade expansion, and cultural renaissance, it simultaneously grappled with economic challenges, including high taxation, middlemen exploitation, and external threats. The study juxtaposes the region's advancements, such as the Zabt system and the architectural legacies of emperors like Jahangir and Shah Jahan, against the backdrop of inherent vulnerabilities and external pressures. In essence, the Mughal influence on Kashmir presents a rich tapestry of growth, integration, challenges, and resilience, offering profound insights into the complexities of regional governance and identity formation within a vast empire. This research serves as a comprehensive exploration of a historically significant period, emphasizing the nuanced interplay between power, culture, and economics in shaping the destiny of a region.